PRAGMATIC FUNCTIONS OF PHRASEOLOGY IN TRANSLATION - Karimova Marjona Alisherovna (TADQIQOTLAR.UZ, 2024)
Annotation: Translating the phraseological units is a complex and challenging task that requires a deep understanding of both the source and target languages. The article discusses the challenges of accurately translating these expressions, which are deeply rooted in the culture and language of the source text. The article also explores different approaches to translating phraseology in  media texts, including the use of equivalent expressions in the target language and providing cultural explanations or footnotes to help the target audience understand the meaning and significance of the expression. The article highlights the importance of considering the pragmatic features of  phraseology  in  media  texts  when  translating  them,  in  order  to  ensure  that  the intended  meaning  and  cultural  references  are  accurately  conveyed  to  the  target audience.